Lesson Studi Pembelajaran Outdoor learning Bagi Guru Sekolah Dasar - Astuti Wijayanti; Aris Munandar (Jurnal Pemberdayaan Masyarakat, 2019)
The environment is the largest natural laboratory in science learning. However, unfortunately, this potential has not been utilized properly. Most science learning is often carried out in the classroom. Therefore, through community service, it is expected to help the difficulties of teachers in planning and implementing outdoor learning in science learning in accordance with the standards of the educational process. This service was carried out for 8 months using the lesson study model through three stages, namely plan (plan), do (implement) and see (reflect) carried out by elementary teachers. The results of dedication show that lesson studies conducted in both elementary schools can provide good service for elementary school teachers in preparing lesson plans and can improve the ability of elementary school teachers in preparing RPP based on outdoor learning processes so that teachers can carry out learning with a new, pleasant, challenging atmosphere and teach.